Analisis Keterampilan Berpikir Kritis Siswa Kelas I pada Pembelajaran IPA di Sekolah Dasar - Puspitasari, Puspitasari; Muttaqijn, M. Imam; Haryati, Haryati (TSAQOFAH, 2024)
This study is entitled "Analysis of Critical Thinking Skills of Grade IV Students in Science Learning in Elementary Schools". The purpose of this study was to determine the critical thinking skills possessed by grade IV students at SDN 03 Muara Ciujung Timur as well as factors that affect students' critical thinking skills. The method in this study uses qualitative using a case study approach with data collection techniques using test, interview, observation and documentation techniques. The results of the research that have been conducted there are 2 students with high critical thinking skills, 3 students with medium critical thinking skills, and 5 students with low critical thinking skills. The results of the test instruments, interviews and student observations have not met the indicators of critical thinking, namely: Activities to formulate questions, Limit problems, Test data, Analyze various opinions, Avoid highly emotional considerations, Avoid excessive simplification, Consider various interpretations, Tolerate ambiguity. Then the factors that influence it are: the internal factors that affect thinking skills are: physical condition, anxiety, intellectual development, and learning motivation while the external factors are: teacher teaching style, teacher teaching strategies and style. The conclusion from the analysis of critical thinking skills of grade IV students in science learning in elementary schools is that students have not beenable to meet critical thinking indicators so it can be said that the level of critical thinking skills of students at SDN 03 Muara Ciujung Timur is low.